2021
DOI: 10.3390/s21030707
|View full text |Cite
|
Sign up to set email alerts
|

A New Dynamical Method for Bearing Fault Diagnosis Based on Optimal Regulation of Resonant Behaviors in a Fluctuating-Mass-Induced Linear Oscillator

Abstract: Stochastic resonance (SR), a typical randomness-assisted signal processing method, has been extensively studied in bearing fault diagnosis to enhance the feature of periodic signal. In this study, we cast off the basic constraint of nonlinearity, extend it to a new type of generalized SR (GSR) in linear Langevin system, and propose the fluctuating-mass induced linear oscillator (FMLO). Then, by generalized scale transformation (GST), it is improved to be more suitable for exacting high-frequency fault features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…which can be comprehended as a function of regulatable parameters γ, ω, σ, λ, and R. It is worth emphasizing that σ and λ are the internal parameters to control SDN intensity and correlation rate, which play an active role in transforming internal noise energy to signal. It is quite different from the passive regulation of conventional SR method [27,35,36], where the noise originates from the external input, and the system only cooperates it and passively transforms its energy to signal by SR mechanism.…”
Section: System Stationary Responsementioning
confidence: 95%
See 1 more Smart Citation
“…which can be comprehended as a function of regulatable parameters γ, ω, σ, λ, and R. It is worth emphasizing that σ and λ are the internal parameters to control SDN intensity and correlation rate, which play an active role in transforming internal noise energy to signal. It is quite different from the passive regulation of conventional SR method [27,35,36], where the noise originates from the external input, and the system only cooperates it and passively transforms its energy to signal by SR mechanism.…”
Section: System Stationary Responsementioning
confidence: 95%
“…All the methods mentioned above follow the framework of the classical SR theory with nonlinearity, periodicity and random force as the basic elements, but this view has been overturned by many studies on generalized SR (GSR) phenomena in recent years, and it is extended it to linear Langevin system by introducing multiplicative noises [27][28][29][30][31][32][33][34]. Thus, Chen et al [35] explored the bearing fault diagnosis method based on a fluctuating-mass linear oscillator, where the internal randomness acting upon the second-order term was introduced to regulate the dynamical behaviors. By analyzing the system stationary response, it was found that the synergy of linear system, internal random regulation and external excitement could generate GSR behaviors, which played an important role in adaptively optimizing the system parameters to improve diagnosis performance of weak fault signal under the strong-noise background.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure that the transformed system has an equivalent dynamical behavior to equation (1), we make the input signal recover to the original strength [28,29]. It is equivalently extended to…”
Section: System Modelmentioning
confidence: 99%
“…with the Grünwald-Letnikov definition of fractional-order derivation; (c) GSR-based scale-transformed linear oscillator (GSR-SLO) [28],…”
Section: Experimental Diagnosismentioning
confidence: 99%
See 1 more Smart Citation